2021
DOI: 10.36418/japendi.v2i7.230
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Dongeng Digital Terhadap Kemampuan Kosakata Bahasa Jawa Krama Anak Usia 5-6 Tahun di Tk Dharma Wanita Ngimbang Lamongan

Abstract: Latar Belakang: Anak usia dini adalah anak yang belum dewasa yang usianya nol sampai sampai enam tahun yang dalam tahap pertumbuhan dan perkembangan yang sangat pesat. Pada tahap anak usia dini ini perkembangan otak anak sangatlah penting Tujuan: Untuk mengetahui pengaruh dongeng digital terhadap kemampuan kosakata bahasa Jawa Krama anak usia 5-6 tahun di TK Dharma Wanita Lamongan. Metode: Menggunakan penelitian kuantitatif, dengan jenis penelitian Pre Eksperimental Design dan desain penelitiannya One Group Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
1
1
0
1
Order By: Relevance
“…The research by Aprilia and Hasibuan (2021), and Hardiyana and Nuryati (2021) which examined the use of fairy tales on children's language skills also corroborated previous findings from Kusdiyati, Halimah, and Azlin (2010) who found that there was an effect of giving fairy tales with hand puppets on Indonesian language skills in children aged 5-6 years.…”
Section: Fuadah Tiara and Pratiwi (2022)supporting
confidence: 83%
See 1 more Smart Citation
“…The research by Aprilia and Hasibuan (2021), and Hardiyana and Nuryati (2021) which examined the use of fairy tales on children's language skills also corroborated previous findings from Kusdiyati, Halimah, and Azlin (2010) who found that there was an effect of giving fairy tales with hand puppets on Indonesian language skills in children aged 5-6 years.…”
Section: Fuadah Tiara and Pratiwi (2022)supporting
confidence: 83%
“…Author(s) Findings Aprilia, Hasibuan (2021) There is an influence of digital fairy tales on the Javanese Krama (Bahasa Jawa Krama) vocabulary skills of children aged 5-6 years at the Kindergarten Dharma Wanita (TK Dharma Wanita) Ngimbang Lamongan…”
Section: Table 1 Findings Of Previous Researchmentioning
confidence: 99%
“…Anak-anak tidak menunjukkan peningkatan dalam tanggung jawab atau pemahaman nilai-nilai yang disampaikan dalam cerita tersebut. (Tri Aprilia & Hasibuan, 2021) mengatakan bahwa Storyteling konvensional memiliki beberapa keterbatasan dalam meningkatka perubahan pada anak-anak. Anak-anak cenderung kurang tertarik dan sulit mempertahankan fokus selama sesi story telling.…”
Section: Hasil Dan Pembahasanunclassified